Repurposing Albendazole and Mebendazole, an antiparasitic drug in treating colorectal cancer- a review - Mondal, Shawon (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2022.